Purificação, caracterização bioquímica e potencial antibacteriano de um inibidor de tripsina de sementes de chia (Salvia hispanica L.) - Souza, Adson Ávila de (2021)
The burgeoning emergence of multiresistant bacteria has been generated the socalled antibiotic resistance crisis with profound global impacts. The presence of resistant strains in the hospital environment has raised healthcare costs and the chances of treatment failures, leading to clinical complications or mortality. Thus, it is imperative to search for alternative therapies to antibiotics that are becoming obsolete. Plant protease inhibitors (PPIs) appear as promising molecules with antimicrobial activity, considered excellent candidates for novel therapeutic agents’ development. This work aimed to purify, biochemically characterize and evaluate the antibacterial activity in vitro of a trypsin inhibitor from chia (Salvia hispanica L.) seeds. The trypsin inhibitor, named ShTI, was purified from chia seeds through crude extract heat treatment, affinity and reversed-phase chromatographies. Tricine-SDS-PAGE analysis of ShTI revealed a single glycoprotein band of ~11 kDa under non-reducing conditions, confirmed by mass spectrometry analysis (11.558 kDa). ShTI was remarkably stable under high-temperature incubation (100 °C; 120 min.), maintaining 100% of its trypsin inhibitory activity. Moreover, the purified trypsin inhibitor was stable at a broad pH range (2 -10), retaining 80 – 100% of inhibitory activity in acidic and basic pHs. Upon exposure to DTT (0.1 M; 120 min.), ShTI antitrypsin activity was partially lost (~38%), indicating the participation of disulfide bridges in the protein native structure. Kinetic studies showed that ShTI is a competitive inhibitor (Ki = 1.79 x 10-8 M; IC50 = 1.74 x 10-8 M) that forms a 1:1 stoichiometry ratio for the ShTI:trypsin complex. In vitro antimicrobial susceptibility, assays demonstrated ShTI antibacterial activity against all three Staphylococcus aureus strains tested (S. aureus ATCC® 6538P, Methicillinresistant S. aureus ATCC® 4996, and a clinical strain of MRSA), showing MIC ranging from 15.83 to 19.03 µM. No significant effect was observed toward the Gram-negative bacteria tested (Escherichia coli ATCC® 8739, Pseudomonas aeruginosa ATCC® 9027). ShTI also displayed antibacterial activity in drug combination therapy with oxacillin Fractional Inhibitory Concentration Index (FICI) ranges from 0.20 to 0.33 showing synergistic effects against S. aureus ATCC® 6538P and MRSA ATCC® 4996. Fluorescence and scanning electron microscopy analysis revealed that ShTI increased cell permeability, leading to plasma membrane pore formation and inducing overproduction of reactive oxygen species in S. aureus. Therefore, ShTI represents a novel candidate to be used as a therapeutic agent for bacterial management of S. aureus infections.